HUBUNGAN ANTARA KUALITAS PELAYANAN, PERCEIVED PRICE, KEPUASAN, DAN LOYALITAS PELANGGAN - Lamidi - (Universitas Slamet Riyadi, 2012)
ABSTRACT The objective of the research are to examine and analyses : (1) effect of service quality to customer satisfaction, (2) effect of service quality to customer loyalty, (3) effect customer satisfaction to customer loyalty, (4) effect of service quality to customer loyalty, through customer satisfaction as the mediating variable, (5) effect of the interaction between service quality and perceived price to customer satisfaction. Population on this research are all customer’s of warung makan Pokwe Bu Trini in Surakarta. The samples of this research consist of 100 customer’s taken with snowball and convenience sampling. The result reveals that (1) there is a significance effect between service quality to customer satisfaction, (2) there is a significance effect between service quality to customer loyalty, (3) there is a significance effect between customer satisfaction to customer loyalty, (4) there is a significance direct effect of the service quality to customer loyalty, through customer satisfaction as the mediating variable, (5) Interaction of the service quality and perceived price has significant effect on customer satisfaction. Keywords: service quality, perceived price, satisfaction, customer loyalty